2020
DOI: 10.1186/s12879-020-05518-1
|View full text |Cite
|
Sign up to set email alerts
|

Veno-venous extracorporeal membrane oxygenation successfully treated a case of severe pulmonary hemorrhage caused by leptospirosis

Abstract: Background Pulmonary hemorrhage is an important complication of leptospirosis. Once acute respiratory distress syndrome (ARDS) occurs as a secondary condition, treatment is extremely difficult and the mortality rate is very high. Case presentation The patient was a 49-year-old. He was admitted to the hospital because he had experienced a fever and cough for 4 days. Hemorrhage, respiratory failure, ARDS and other symptoms appeared soo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Through literature search, we realized that antibiotics related to the development of JHR not only include penicillins, tetracyclines and erythromycin, but also newer antimicrobial agents such as cephalosporins, levofloxacin, ciprofloxacin, clarithromycin, meropenem, and azithromycin can also cause JHR [ 1 ]. To prove the relationship between leptospirosis and JHR and predict the characteristics of patients with severe types, we searched and reviewed the presentation of five adults with pulmonary hemorrhagic leptospirosis, and found that they all showed aggravation of existing symptoms or the occurrence of new symptoms that cannot be explained by the progression of the disease [ [2] , [3] , [4] , [5] , [6] ]. However, they survived after active symptomatic treatment ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Through literature search, we realized that antibiotics related to the development of JHR not only include penicillins, tetracyclines and erythromycin, but also newer antimicrobial agents such as cephalosporins, levofloxacin, ciprofloxacin, clarithromycin, meropenem, and azithromycin can also cause JHR [ 1 ]. To prove the relationship between leptospirosis and JHR and predict the characteristics of patients with severe types, we searched and reviewed the presentation of five adults with pulmonary hemorrhagic leptospirosis, and found that they all showed aggravation of existing symptoms or the occurrence of new symptoms that cannot be explained by the progression of the disease [ [2] , [3] , [4] , [5] , [6] ]. However, they survived after active symptomatic treatment ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…It can detect Leptospira DNA in specimens quickly and accurately during the early stage of the infection. 21,22 Fifteen other reports [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] have described different diagnostic methods for severe leptospirosis requiring extracorporeal membrane oxygenation. As shown in Table 2, PCR, the MAT, ELISA, and NGS can be used to diagnose severe leptospirosis early.…”
Section: Discussionmentioning
confidence: 99%
“…ECMO support in severe leptospirosis was previously described as an effective treatment for reducing patient mortality. Twelve recent case reports describe the use of a V-V ECMO in patients with leptospirosis complicated by ARDS and hemorrhagic pneumonia; only one patient died [ 6 , 18 , 19 , 20 ]. Two case reports described the use of V-A ECMO in two patients affected by complicated leptospirosis with (1) right ventricular overload and myocarditis and (2) cardiogenic shock and pulseless electrical activity, respectively.…”
Section: Discussionmentioning
confidence: 99%